EP823 Patients with stage IV epithelial ovarian cancer: Understanding the determinants of survival. (1st November 2019) - Dabi, Y; Huchon, C; Ouldamer, L; Bendifallah, S; Collinet, P; Bricou, A; Daraï, E; Ballester, M; Lavoué, V; Haddad, B; Touboul, C; ,
Abstract : Introduction/Background: The most appropriate management for patients with stage IV ovarian cancer remains unclear. Our objective was to understand the main determinants associated with survival and to discuss best surgical management in these patients. Methodology: Data of 1038 patients with confirmed ovarian cancer treated between 1996 and 2016 were extracted from maintained databases of 7 French referral gynecologic oncology institutions. Patients with stage IV diseases were selected for further analysis. The Kaplan Meier method was used to estimate the survival distribution. A Cox proportional hazards model including all the parameters statistically significant in univariable analysis, was used to account for the influence of multiple variables. Results: Two hundred and eight patients met our inclusion criteria: 65 (31.3%) never underwent debulking surgery, 52 (25%) underwent primary debulking surgery (PDS) and 91 (43.8%) neoadjuvant chemotherapy and interval debulking surgery (NACT-IDS). Patients not operated had a significantly worse overall survival than patients that underwent PDS or NACT - IDS (p<0.001). In multivariable analysis, three factors were independent predictors of survival: upfront surgery (HR 0.32 95% CI 0.14–0.71, p=0.005), postoperative residual disease=0 (HR 0.37 95% CI 0.18–0.75, p=0.006) and association of Carboplatin and Paclitaxel regimen (HR 0.45 95% CI 0.25–0.80, p=0.007). Conclusion: Presence of distant metastases should not refrain surgeons from performing radical procedures, whenever the patient is able to tolerate. Maximal surgical efforts should be done to minimize residual disease as it is the main determinant of survival. Disclosure: Nothing to disclose.